Effects of progressed and nonprogressed volume-based overload plyometric training on components of physical fitness and body composition variables in youth male basketball players - Palma-Muñoz, I.; Ramirez-Campillo, R.; Azocar-Gallardo, J.; Álvarez, C.; Asadi, A.; Moran, J.; Chaabene, H. (The Journal of Strength and Conditioning Research, 2021)
This study examined the effect of 6 weeks of progressed and nonprogressed volume-based overload plyometric training (PT) on components of physical fitness and body composition measures in young male basketball players, compared with an active control group. Subjects were randomly assigned to a progressed PT (PPT, n = 7; age = 14.6 ± 1.1 years), a non-PPT (NPPT, n = 8, age = 13.8 ± 2.0 years), or a control group (CG, n = 7, age = 14.0 ± 2.0 years). Before and after training, body composition measures (muscle mass and fat mass), countermovement jump with arms (CMJA) and countermovement jump without arms (CMJ), horizontal bilateral (HCMJ) and unilateral jump with right leg (RJ) and left leg (LJ), 20-cm drop jump (DJ20), sprint speed (10 m sprint), and change of direction speed (CODS [i.e., T-test]) were tested. Significant effects of time were observed for muscle and fat mass, all jump measures, and CODS (all p < 0.01; d = 0.37-0.83). Significant training group × time interactions were observed for all jump measures (all p < 0.05; d = 0.24-0.41). Post hoc analyses revealed significant pre-post performance improvements for the PPT (RJ and LJ: Delta 18.6%, d = 0.8 and Delta 22.7%, d = 0.9, respectively; HCMJ: Delta 16.4%, d = 0.8; CMJ: Delta 22.4%, d = 0.7; CMJA: Delta 23.3%, d = 0.7; and DJ20: Delta 39.7%, d = 1.1) and for the NPPT group (LJ: Delta 14.1%, d = 0.4; DJ20: Delta 32.9%, d = 0.8) with greater changes after PPT compared with NPPT for all jump measures (all p < 0.05; d = 0.21-0.81). The training efficiency was greater (p < 0.05; d = 0.22) after PPT (0.015% per jump) compared with NPPT (0.0053% per-jump). The PPT induced larger performance improvements on measures of physical fitness as compared to NPPT. Therefore, in-season progressive volume-based overload PT in young male basketball players is recommended.